Thailand : Public Finance Review - World Bank (Washington, DC, 2013)
The report assesses the performance of Thailand's fiscal institutions, in responding to the pressures of the economic crisis, and its likely performance in meeting the challenges of the new Constitution, and in modernizing the public sector. It builds on the analysis conducted to design the Government's Public Sector Management Reform Program, and lays the foundation for reform options. By examining policy responses, identifying institutional shortcomings, and reviewing challenges for fiscal policy and administration during the economic crisis, lessons are drawn from its experience, focusing attention on selective issues, such as human resource management, and tax policy reforms, while serving as a practical compendium of reforms currently underway, and suggesting priorities for further reform. The country's public expenditures and development outcomes are examined, with special attention on expenditure planning and fiscal risk management, identifying the foundation for fiscal decentralization, and its reform strategy.